2019
DOI: 10.1186/s12886-019-1157-3
|View full text |Cite
|
Sign up to set email alerts
|

Long term effect of phacoemulsification on intraocular pressure in patients with medically controlled primary open-angle glaucoma

Abstract: Background The effect of cataract surgery on IOP in patients with primary open-angle glaucoma (POAG) is a subject of debate. We investigated the effect of cataract surgery by phacoemulsification on intraocular pressure (IOP) in patients with medically POAG . Methods Seventy eyes of 40 POAG patients undergoing cataract surgery by phacoemulsification were retrospectively evaluated. All patients had their POAG medically controlled without prior glaucoma surgery. Baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
(40 reference statements)
2
31
0
Order By: Relevance
“…Previous studies showed 6-26% of patients had increase in postoperative IOP and 4-26% of patients needed increase in IOP-lowering medication at 1-5 years following phacoemulsification [23][24][25][26][27][28]. In this present study we found 17% OAG eyes with a postoperative IOP increase…”
Section: Plos Onesupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies showed 6-26% of patients had increase in postoperative IOP and 4-26% of patients needed increase in IOP-lowering medication at 1-5 years following phacoemulsification [23][24][25][26][27][28]. In this present study we found 17% OAG eyes with a postoperative IOP increase…”
Section: Plos Onesupporting
confidence: 60%
“…Chen et al demonstrated 13% IOP reduction in eyes with primary open angle glaucoma (POAG) following phacoemulsification alone [23]. But other reports revealed considerable variability of outcomes with postoperative IOP reduction ranging from 7 to 22% [24,25]. The different study designs and the variability of inclusion and exclusion criteria may account for this.…”
Section: Plos Onementioning
confidence: 99%
“…The small discrepancy between the studies can probably be attributed, among other factors, to different mean baseline IOP values. In patients with POAG, similar analyses of long-term effects showed a slightly different IOP reduction one year after the procedure: by 1.15 ±3 mmHg (6.8 ±18.1%) [17], by 1.0 ±5.5 [12], or by 13% [18]. A large metaanalysis found that the mean reduction in IOP noted at 6, 12, 24 and 36 months after the surgery was 12%, 14%, 15% and 9% from the baseline, respectively [14].…”
Section: Discussionmentioning
confidence: 81%
“…In a recently published paper, a decrease in the number of medications was achieved in 17.1% of patients. A total of 7.2% patients required additional glaucoma medications, and in 75.7% of patients with POAG the number of medications remained unchanged [17]. Reducing the dependence on glaucoma medications limits their adverse effects on the ocular surface [14], leading to improved patient comfort and potentially increasing therapeutic compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A sizeable proportion of medically controlled glaucoma patients with open angles undergoing phacoemulsification experienced a rise in IOP or required more aggressive treatment to regulate IOP postoperatively. 13,14 In contrast to this, our study did not take into account the pre-operative medical treatment of glaucoma into consideration.…”
Section: Discusionmentioning
confidence: 99%